Population dynamics of flocculating yeasts - Mota, M. (1994)
The problem of understanding the recognition and specific interactions in a population of yeast flocculating cells is discussed. The biochemistry, physiology and genetics of flocculation is briefly reviewed. Yeast flocculation requires the expression of a specific protein (lectin) on flocculent cells, and carbohydrate (receptors) on neighbouring cells. Adhesion experiments performed with cells whose flocculation is repressed by growth conditions, indicating that the inhibition of flocculation is due to inhibition or inactivation of lectin-like component. Additionally, using adhesion experiments, it is demonstrated that cells of non-flocculent strain interact by establishing a true bond with flocculent cells rather than by entrapment inside the floc matrix. As phenotypic expression of flocculation, for several strains, is shown to be repressed, modulated or induced by modifying growth conditions, the constitutiveness and inducibility of flocculation are also discussed.